2017
DOI: 10.2217/fmb-2017-0087
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Host Proteins Interacting with Escherichia Coli O157:H7 EspF using Bimolecular Fluorescence Complementation

Abstract: Aim:To screen host proteins that interact with enterohemorrhagic Escherichia coli O157:H7 EspF. Materials & methods: Flow cytometry and high-throughput sequencing were used to screen interacting proteins. Molecular function, biological processes and Kyoto Encyclopedia of Genes and Genomes pathways were studied using the DAVID online tool. Glutathione S-transferase pull down and dot blotting were used to verify the interactions. Results: 293 host proteins were identified to associate with EspF. They were mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 88 publications
5
17
0
Order By: Relevance
“…Ying have found that EspF has the ability to interact with featured ribosomal proteins and to modulate the antiphagocytosis process by bonding with ANXA6 (Hua et al, 2018b). In our study, we found that SNX9, SNX18, 14-3-3 epsilon, ANXA6, ANXA2 and EHEC O157:H7 EspF proteins also interact.…”
Section: Discussionsupporting
confidence: 57%
“…Ying have found that EspF has the ability to interact with featured ribosomal proteins and to modulate the antiphagocytosis process by bonding with ANXA6 (Hua et al, 2018b). In our study, we found that SNX9, SNX18, 14-3-3 epsilon, ANXA6, ANXA2 and EHEC O157:H7 EspF proteins also interact.…”
Section: Discussionsupporting
confidence: 57%
“…EspF's role in causing diarrhea is the ability to disrupt TJs, but the precise mechanism of EspF's binding to host proteins to cause diarrhea has not been defined. In our previous research, we screened AQP7P2, a type of water channel protein that interacts with EspF (Hua et al, 2018 ). Their interaction may induce diarrhea by changing the activity of water molecule transport.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we screened and verified that Annexin A6 (Anxa6) interacts with EHEC O157:H7 EspF using Bimolecular Fluorescence Complementation (BiFC) technology for the first time (Hua et al, 2018 ). Anxa6 belongs to a highly conserved protein family characterized by calcium-dependent binding to phospholipids.…”
Section: Inhibition Of Phagocytosismentioning
confidence: 99%
“…As EspF is involved in TER disruption, we hypothesized that EspF would interact with a specific host protein to interfere with the pathogenic phenotype. In our previous study, we employed the bimolecular fluorescence complementation (BiFC) method to examine the interplay between EspF and host proteins, which provided specific candidates that interact with EspF (Hua et al, 2018b). Among these candidates, ANXA6 showed a strong positive reaction with EspF.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive evidence implicating EspF in the disruption of TJ barrier structure and function, a detailed molecular mechanism has not yet been elucidated. Our previous study demonstrated that host protein-Annexin A6 (ANXA6) co-precipitated with EspF (Hua et al, 2018b). ANXA6 is a scaffold protein that links the membrane microdomains with the cell cytoskeleton organization (Grewal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%